The normative underpinnings of Ireland's proposed regulation of assisted human reproduction. (10th November 2022) - Bracken, Lydia
Abstract: Assisted human reproduction (AHR) challenges traditional understandings of family relationships. Yet, the Irish legislature remains focused on normative constructions of the family and has relied on this understanding as the basis to determine the sort of legal family relationships that it will accommodate in AHR under the Health (Assisted Human Reproduction) Bill 2022. The result is a Bill that adopts a binary view of reproduction that fails to align with broader legal and social developments. The Bill is also exclusionary as it seeks to limit access to AHR treatment to those families that replicate (or have the potential to replicate) the sexual family form. This article examines the normative underpinnings of the 2022 Bill by analysing the gendered language that is used to refer to different aspects of the reproductive process and by critiquing the provisions that restrict access to AHR treatment for certain intending parents. The article challenges the entrenchment of the sexual family in the legal imagination, arguing that there is a need to rethink the approach adopted in the 2022 Bill to ensure that the proposed legislation will accommodate the diverse range of families who will seek to rely on its provisions.